Tourney set to be a nail-biting affair - The Star, Ng Wei Loon (2010)
The champions and the runners-up from three zones are setting a date for re-matches after they were drawn into the same group for the final rounds of the inaugural Higher Education Minister Cup tournament from July 17 to 25.